2006
DOI: 10.1681/asn.2005101051
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Analyses of Membrane Cofactor Protein (CD46) Mutations in Atypical Hemolytic Uremic Syndrome

Abstract: Hemolytic uremic syndrome (HUS) isAs in other studies, incomplete penetrance is shown, suggesting that MCP is a predisposing factor rather than a direct causal factor. The low level of recurrence of aHUS in transplantation in patients with MCP mutations is confirmed, and the first MCP null individuals are described. This study confirms the association between MCP deficiency and aHUS and further establishes that a deficiency in complement regulation, specifically cofactor activity, predisposes to severe thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
187
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(202 citation statements)
references
References 34 publications
(53 reference statements)
11
187
2
1
Order By: Relevance
“…All exons of the complement regulatory genes were sequenced as described previously (7,(27)(28)(29). The primer sequences for CFH, CFI, MCP, CFB, C3, and C4BP gene screening are available from the authors on request.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…All exons of the complement regulatory genes were sequenced as described previously (7,(27)(28)(29). The primer sequences for CFH, CFI, MCP, CFB, C3, and C4BP gene screening are available from the authors on request.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…Among the reported cases, approximately 50% had mutations of the complement regulatory proteins factor H (CFH) (7)(8)(9)(10)(11)(12), membrane cofactor protein (13)(14)(15), or factor I (16)(17)(18); mutations occurred less frequently in factor B (19), C3 (20), and thrombomodulin (21).…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57][58] Complement system mutations can be implicated in up to 52% of patients who have aHUS. 59 Many different variants in complement genes have been reported to predispose to aHUS, 60-63 such as complement factor H (CFH), 64,65 factor I (CFI), 66,67 C3, 68 thrombomodulin (THBD), 60 membrane cofactor protein (MCP or CD46) 69,70 and factor B (CFB). 71 It was shown that patients who have a mutation in MCP carry the best prognosis, as compared with other genetic abnormalities, and almost all of the above genetic mutations are heterozygous.…”
Section: Role Of Genetic Mutations In Post-bmt Tmamentioning
confidence: 99%